Small gift, big smile: mitologia do presente nas práticas e gosto de consumo - Magalhães, Maria Cecília Palma (2012)
This research aims at the deduction of an axiology of contemporary living expericences in consumption practices, specifically in the commerce of Sanrio s small gifts, imprinted with Hello Kitty character. This way, we seek to understand through it wide mediatic reach the means by which the brand funds social archetypes in the purchase and use of its products. As the theoretical and methodological background we propose discursive semiotics as a social action theory, offering subsidies related to the consumption study in capitalist societies. The research is guided by Greimas narrative semiotics postulations, in the same way as the advances that guide significance understanding as the sensitive experience of life practices. Simultaneously we approach Sanrio s manifestation through Floch s plastic and figurative semiotics as a bricolage an enunciation of the culturalized world. In order to better understand the consumption performances, Landowski s sociosemiotics is proposed as an analytical fundament of not only intersubjective relations, but sociabilities interactions and consumers modalizations as a form of taste and contemporary lifestyles. Progressively will be analyzed: (1) the brand s identity visibility and its symbolic repercussions; (2) Hello Kitty s presence as the brand s spokesperson and its manifestation in the product lines; (3) sensitive interactions promoted among consumers in the sharing of images and the brand s ownership, in the contemporary stage of social enactments, the digital space. In the construction of archetypes motivated by the purchase and hoarding that identifies and homologates identities we can catch a glimpse on the brand s visibilities as a social way of existing. Nourished by capitalist society, Sanrio elaborates new components of small contemporary mythologies